MUSEUM TELEKOMUNIKASI SELULER DI KOTA SURAKARTA - Rosy, Papin Longaun; Muqoffa, Mohamad; Samsudi, Samsudi (Universitas Sebelas Maret Surakarta, 2016)
Nowadays cellular telecommunications has become one in our everyday activity. Cellular telecommunications is a method of communication over long distances using electromagnetic media that is divided into sections called cells. Issues underlying planning and design of the Cellular Telecommunications Museum in Surakarta, including the excessive use of cellular devices in Indonesia; high levels of cellular devices disposal that are not used but still feasible to use; indifference of society towards the use of cellular devices; the necessity for a place that act as information media for society and to take care the cellular devices; and the potentials of Surakarta as the museum site as seen from its history, economics, and social to cellular telecommunications. Design problem that arise from the existing issue is how to plan the museum as a place to storage, preservation, exhibitions, and educational for the cellular telecommunications technology in Surakarta. The objective of this design is to get the museum design as a place to storage, preservation, exhibitions, and educational for the cellular telecommunications technology in Surakarta. The result obtained is a museum design as a place to storage, preservation, exhibitions, and educational for the cellular telecommunications technology that can contribute on the use and maintenance of old mobile devices that are still feasible to use to the public through the focus of attracting public attention to visit the museum by the use of design aesthetic and arrangement of museum rooms which displays the features of cellular technology as a matter of museum collections, and also providing a place to supporting activities related to cellular technology. Keyword: Cellular Device, Cellular Telecommunications. Exhibitions, Education, History, Preservation, Museum, Storage.